BUSINESS DEVELOPMENT OF CARDIOVASCULAR CENTER OF EXCELLENCE AT CIKALONGWETAN REGIONAL PUBLIC HOSPITAL - Sari, Devy Ike Mustika; Hendri, Meriza (Politeknik Negeri Ambon, 2025)
Introduction: Cardiovascular disease is the leading cause of death in both Indonesia and the world. However, West Bandung Regency still lacks adequate specialized referral services. RSUD Cikalongwetan is responding to this urgent need by developing a business plan for establishing a premier cardiovascular care unit. This study aims to formulate a business strategy by analyzing internal and external environments, marketing, finance, operations, human resources, and investment feasibility based on key financial indicators. Methods: The research employs a descriptive qualitative method, utilizing techniques such as observation, internal document review, and secondary data analysis from the Ministry of Health and the World Health Organization (WHO). Analytical tools used include SWOT, IFAS-EFAS, Design Thinking, the Business Model Canvas, and the Timmons Model. Financial projections are evaluated using Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, Return on Investment (ROI), and Profitability Index. Results: The results indicate a strong market growth potential with a compound annual growth rate (CAGR) of 30.79% and a Net Profit Margin of 6.68%. The investment proves highly feasible, with a positive NPV, an IRR of 45%, a Payback Period of 1 year and 11 months, and a Profitability Index of 2.14. The ROI is 146.23%, strong mid-term profitability, and financial efficiency. RSUD Cikalongwetan also demonstrates strengths in referral network integration, cost control, and human resource readiness. The development of cardiovascular services at RSUD Cikalongwetan presents both high business and social potential. With a focused strategy, interdepartmental synergy, and stakeholder support, the service is poised to become a reliable regional referral center. It is recommended that the hospital strengthen clinical coordination systems, accelerate investment in diagnostic equipment, and foster cross-sector strategic collaborations to ensure long-term sustainability. Keywords: Business Planning, Cardiovascular Services, Hospital, Healthcare Strategy.